Effects of shade, water and species mix on perennial ryegrass and red clover competition - Lissbrant, Sofia (2005)
A silvopasture system is an agroforestry system specifically designed for the production of trees, tree products, forage for grazing and livestock. Research has shown that silvopasture systems can be an environmentally and economically feasible alternative to traditional land uses.